‘Enjoyable’, ‘okay’, or ‘like drawing teeth’? Chinese and British Students’ Views on Writing Assignments in UK Universities - Leedham, Maria (Journal of Academic Writing, 2014)
Research in academic writing is a growing field within Applied Linguistics, yielding a wide range of conferences, journal publications and books. However, comparatively little work has been conducted on students’ attitudes towards the production of writing for assessment. This article reports findings from a questionnaire study of Chinese and British students (n=202) across 37 UK universities. The study aims to uncover the extent to which students feel they were prepared for tertiary-level writing, how useful they find assignment-writing, and whether they enjoy this activity. The focus of the article is on the similarities and differences in attitudes towards assessed writing given by the two student groups. Chinese students were selected as a contrast to British students as the former are now the ‘largest single overseas student group’ in the UK with more than 60,000 Chinese people studying in 2008 (The British Council, 2010). Detailed, open-ended responses from the questionnaire were coded and followed up with email and face-to-face interview questions with a subset of students (n=55). The findings indicate that neither student group feel well-prepared for the challenges of tertiary-level writing, and reveal a depth of feeling regarding the enjoyment and perceived utility - or otherwise - of academic writing.